Smartphone Applications for Reproduction: From Rigorously Validated and Clinically Relevant to Potentially Harmful - Carol Lynn Curchoe (European Medical Journal, 2020)
Infertility practitioners are increasingly turning to mobile applications (apps) to help improve patient care. Provider-facing apps range from reference to communication tools, to versions of the electronic health record. Some available evidence indicates that mobile apps facilitate patient care by increasing efficiency and accuracy in documentation, information retrieval, and coordination of care.1 The U.S. Food and Drug Administration (FDA) website currently lists dozens of cleared or approved applications for mobile 'medical device' apps, and reproductive healthcare has also certainly benefitted from this explosion in mobile technology. Reproductive and fertility-focussed apps now aim to treat and diagnose disease, aid clinical decision-making, and manage patient care. Infertility patients may use apps pretreatment to manage lifestyle factors, during treatment to manage medications and calendar appointments, and for message boards where they can share experiences, and seek or offer peer support. Here, the authors review the history of medical health and research apps, current reproduction-specific mobile applications, and discuss the implications of mobile technology for diagnostic point-of-care, clinical research, and patient health management.